Thermodynamic and economic evaluation of an innovative electricity storage system based on thermal energy storage. (May 2020) - Attonaty, Kévin; Pouvreau, Jérôme; Deydier, Alexandre; Oriol, Jean; Stouffs, Pascal
Abstract: One of the main issues concerning the inclusion of renewable energies as a way to produce electricity is the fluctuation of the production. This explains why there is a need for efficient solutions which will allow to store the energy when there is no need for it and release it when renewable energies are not able to sustain the production. This work concerns a Power-to-Power solution based on thermal energy storage at high temperature (around 900 °C). It relies on a simple heating loop to convert electrical energy into heat, and a thermodynamic cycle such as a gas cycle or a combined cycle to convert heat into electricity. One of the questions raised by this system is how it can be profitable from the economic point of view. Indeed a lot of studies have been conducted on energy storage, but very few propose solutions which can be relevant in terms of global costs and payback time. The aim of this study is to investigate if this system could be competitive in the European, and more specifically, French energy market. To look further into this topic, the system architecture and its components are defined. A thermodynamic model is also built to represent the behavior of the cycle. Finally, an economic discussion is performed using cost functions from the literature. The results show that the system does not accumulate enough running hours to justify high investment costs and should rely on simple technologies to insure its profitability. Furthermore, while the high capital expenditures of the whole system could be challenging, the thermal storage itself is not a big expense when compared to the cost of a natural gas fired power plant. Highlights: An innovative solution based on thermal energy storage is introduced. A thermoeconomic analysis is performed. Improving the thermal efficiency does not necessarily lead to cost improvement. The most profitable case is the one which only implies a gas cycle for the discharging phase (LCOE = 149 /MWh). The levelized cost of energy seems to be competitive with more established solutions.